Modulating Crossover Frequency and Interference for Obligate Crossovers in Saccharomyces cerevisiae Meiosis. Issue 5 (1st May 2017) - Chakraborty, Parijat; Pankajam, Ajith V; Lin, Gen; Dutta, Abhishek; Krishnaprasad, G Nandanan; Tekkedil, Manu M; Shinohara, Akira; Steinmetz, Lars M; Nishant, K Thazath
Abstract: Meiotic crossover frequencies show wide variation among organisms. But most organisms maintain at least one crossover per homolog pair (obligate crossover). In Saccharomyces cerevisiae, previous studies have shown crossover frequencies are reduced in the mismatch repair related mutant mlh3 Δ and enhanced in a meiotic checkpoint mutant pch2 Δ by up to twofold at specific chromosomal loci, but both mutants maintain high spore viability. We analyzed meiotic recombination events genome-wide in mlh3 Δ, pch2 Δ, and mlh3 Δ pch2 Δ mutants to test the effect of variation in crossover frequency on obligate crossovers. mlh3 Δ showed ∼30% genome-wide reduction in crossovers (64 crossovers per meiosis) and loss of the obligate crossover, but nonexchange chromosomes were efficiently segregated. pch2 Δ showed ∼50% genome-wide increase in crossover frequency (137 crossovers per meiosis), elevated noncrossovers as well as loss of chromosome size dependent double-strand break formation. Meiotic defects associated with pch2 ∆ did not cause significant increase in nonexchange chromosome frequency. Crossovers were restored to wild-type frequency in the double mutant mlh3 Δ pch2 Δ (100 crossovers per meiosis), but obligate crossovers were compromised. Genetic interference was reduced in mlh3 Δ, pch2 Δ, and mlh3 Δ pch2 Δ. Triple mutant analysis of mlh3 Δ pch2 Δ with other resolvase mutants showed that most of the crossovers in mlh3 Δ pch2 Δ are made through the Mus81 -Mms4 pathway. These results are consistent with a requirement for increased crossover frequencies in the absence of genetic interference for obligate crossovers. In conclusion, these data suggest crossover frequencies and the strength of genetic interference in an organism are mutually optimized to ensure obligate crossovers.